IMPROVING INTEGRITY HALAL SUPPLIER IN FOOD SUPPLY CHAIN: SCOPING REVIEW (Journal of Technology and Operations Management, 2024)
Ensuring integrity in a halal supplier is important for maintaining the trust of consumers who seek halal products. Any compromise in the integrity of the supplier can lead to a loss of confidence in the halal status of their products. In this review will identify what the main key finding will increase integrity in supplier and the objective of this review is to produce a comprehensive mapping next future research and the main themes related to halal supplier in food supply chain. Method: A scoping review of the literature was conducted between 2018 and 2023 using the Web of Science (WOS) and Scopus databases to identify what is the nature of published scientific literature on this topic. A total of 13 journal articles were identified for a full review. Result: Five themes were found from the literaturerelevant to food supply chain integrity through halal supplier. The main themes include perceive value, transparency, technology, standard of procedure and supplier integration. The review indicates that most of the studies are conducted in understanding the supplier efficiency in supply chain. Conclusion: The emergence of findings regarding suppliers in the halal food supply chain will assist in the investigation of halal providers, while also providing significant insights for researchers and practitioners in their respective fields. Moreover, these reviews will be helpful in the supervision of suppliers in the halal food supply chain. This offers future research to more comprehensive research is required to further investigate the performance of halal supplier in food supply chain.